Tourism and community sustainability: The case of Senneterre, Quebec. - Georgescu, Denisa Cristina. (University of Ottawa (Canada), 1998)
This thesis analyzes the potential of recreation and tourism development in Senneterre and examines if it can compensate for the downturn of its traditional forest-based economy and contribute to its long-term sustainability. More specifically, the research focuses on the current supply of and demand for the main recreation and tourism assets (attractions, services and infrastructure, promotion, and hospitality) within the community. Attention is given to the strengths and weaknesses of both supply and demand. The community leaders' perceptions and support of recreation and tourism development as sustainable initiatives for Senneterre are also investigated. The research methodology combines archival research of governmental and non-governmental documents related to recreation and tourism in the Abitibi-Temiscamingue region and survey research involving key representatives of the community. The survey includes informal, exploratory interviews with purposefully selected community members and mailed questionnaires to knowledgeable representatives of various groups such as business people and politicians, recreation and tourism providers, as well as representatives of the First Nations. In this research, a literature review also serves as an important source of information regarding major issues concerning forest dependent communities, sustainable rural tourism, and community development. (Abstract shortened by UMI.)
Keywords: Geography.